2014
DOI: 10.1289/ehp.1306639
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and Barriers to Large-Scale Uptake of Improved Solid Fuel Stoves: A Systematic Review

Abstract: Background: Globally, 2.8 billion people rely on household solid fuels. Reducing the resulting adverse health, environmental, and development consequences will involve transitioning through a mix of clean fuels and improved solid fuel stoves (IS) of demonstrable effectiveness. To date, achieving uptake of IS has presented significant challenges.Objectives: We performed a systematic review of factors that enable or limit large-scale uptake of IS in low- and middle-income countries.Methods: We conducted systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
201
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(211 citation statements)
references
References 47 publications
10
201
0
Order By: Relevance
“…Exposure to IAP is linked to several adverse health effects including acute respiratory infection, chronic obstructive lung disease, pregnancy complications, daily discomfort in women from coughs, headaches, stinging eyes and backaches. The supply of alternative energy services could positively benefit maternal health and reduce child mortality (Beyene and Koch, 2013;USAID, 2010;Anhalt and Holanda, 2009;Duflo and Greenstone, 2008;MoFED, 2010;Barnes et al, 2012 andRehfuess et al, 2014). A study in Mexico has shown that, stoves can reduce IAP by 70 percent, reducing the risk of a range of health impacts.…”
Section: The Roles Of Fuel Efficient Stovementioning
confidence: 99%
See 3 more Smart Citations
“…Exposure to IAP is linked to several adverse health effects including acute respiratory infection, chronic obstructive lung disease, pregnancy complications, daily discomfort in women from coughs, headaches, stinging eyes and backaches. The supply of alternative energy services could positively benefit maternal health and reduce child mortality (Beyene and Koch, 2013;USAID, 2010;Anhalt and Holanda, 2009;Duflo and Greenstone, 2008;MoFED, 2010;Barnes et al, 2012 andRehfuess et al, 2014). A study in Mexico has shown that, stoves can reduce IAP by 70 percent, reducing the risk of a range of health impacts.…”
Section: The Roles Of Fuel Efficient Stovementioning
confidence: 99%
“…Educational status also plays a significant role in determining fuel choice. In addition, the higher education leads to better knowledge regarding modern fuels which could result in a greater likelihood of fuel-switching (ManyoPlange, 2011;Jan, 2012 andRehfuess et al, 2014). High wood prices or scarce supplies of wood are also factors which increase the likelihood of stove adoption (Barnes et al, 1994).…”
Section: Factors Affecting the Adoption Of Fuel Efficient Stovesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main fuel used by households for cooking during the study was firewood and 88 percent of the respondents cook on three stone fireplaces whilst the remaining 12 percent cook on energy efficient cookstoves. In urban areas for example, it is commonplace for men to pay for fuel, while in rural areas it was usually obtained free of cost by women but its collection was associated with significant opportunity costs in the form of lost time for income generation and other productive activities as noted by our respondents: According to Rehfuess et al [36], the uptake of energy efficient stoves tends to be higher in settings where fuel is mostly purchased. The second most widely used fuel reported by respondents was charcoal which is transported in bags on trucks from sites of production to various retail locations so its price is often influenced by transportation costs.…”
Section: "My Wife…was Experiencing Pains In Her Eyes and When I Toomentioning
confidence: 87%